2023
DOI: 10.1108/jhtt-12-2020-0321
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Vietnamese consumers’ perception and word-of-mouth intentions towards Airbnb

Abstract: Purpose This paper aims to provide a comprehensive understanding of Vietnamese consumers’ perceived value and to explore the relationships between its constructs, satisfaction and (e)word-of-mouth (WOM) intentions towards Airbnb. Moreover, the relationship between traditional WOM and electronic WOM (eWOM) was also investigated. Design/methodology/approach An electronic survey was applied to collect data on a sample of Vietnamese Airbnb guests. A total of 352 questionnaires were collected, from which 163 elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Surprisingly, unlike prior research which (Legohérel, 2015; Munar and Jacobsen, 2014; Parra-López et al , 2011) finds that PU positively influences tourists’ intention of using or adopting travel-related technologies, this paper does not find the significant influence of PU on INT in heritage context. However, another study identifies similar results, which indicate that social benefit does not affect tourists’ eWOM intention (Do and Pereira, 2023). Results present a nonsignificant influence of PEOU on INT, which is contrary to the study of Bilgihan et al (2016).…”
Section: Discussionmentioning
confidence: 76%
“…Surprisingly, unlike prior research which (Legohérel, 2015; Munar and Jacobsen, 2014; Parra-López et al , 2011) finds that PU positively influences tourists’ intention of using or adopting travel-related technologies, this paper does not find the significant influence of PU on INT in heritage context. However, another study identifies similar results, which indicate that social benefit does not affect tourists’ eWOM intention (Do and Pereira, 2023). Results present a nonsignificant influence of PEOU on INT, which is contrary to the study of Bilgihan et al (2016).…”
Section: Discussionmentioning
confidence: 76%
“…In this context, prior studies have highlighted the positive association between customer satisfaction and word-of-mouth in various contexts. For instance, Andersen et al (2023), Do et al (2023), andZaato et al (2023) found consistent evidence that satisfied customers are more likely to engage in word-of-mouth communication. This contributes to positive recommendations about their actual experiences (Wei et al, 2023).…”
Section: Discussionmentioning
confidence: 94%
“…Internally, customer satisfaction is gauged through an assessment of service levels and quality that customers anticipate from exiting or previous transactions (Siallagan, 2023). As such, positive customer satisfaction not only encourages favorable WOM referrals but also increases the likelihood of repeat business and enhances loyalty levels (Do & Pereira, 2023). Further, it reflects sentiments arising from products' performance assessments against customer expectations (Veloso & Gomez-Suarez, 2023).…”
Section: Customer Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include product quality (Mouloudj & Bouarar, 2021), emotional value, social value, conditional value, epistemic value (Aravindan et al, 2023), brand love (Niyomsart & Khamwon, 2015), social influence, and perceived value (Mouloudj & Bouarar, 2021). In Vietnam, studies have also found that customer satisfaction (Do & Pereira, 2023), festival attractiveness (Nghi et al, 2021), brand awareness, and brand attitude (Anh, 2022) play a significant effect on WoM. Regarding green products, some factors have been proven to have a significant impact on WoM, such as visual display and environmental ergonomics (Rini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%